Outdoor walking better? environmental elements of cardiorespiratory fitness training trails - Li, Ching; Lee, Chia-Wen; Tsang, King Tai (Frontiers in Sports and Active Living, 2023)
In metropolitan areas where land resources are scarce, trails are a more suitable environment for cardiorespiratory fitness training for modern people. Previous studies have demonstrated that cardiorespiratory fitness is an important factor in assessing individual health and have focused on individual training performance, but the relationship between environment and cardiorespiratory fitness training participants has rarely been investigated. The purpose of this study was to investigate the demands for outdoor cardiorespiratory fitness training and a favorable trail environment by comparing the differences in exercise intensity and perceptions between outdoor and indoor environments. In this study, information on physical data, psychological feedback, and visual atmosphere was collected from nine participants during each phase of moderate intensity cardiorespiratory fitness training in indoor and outdoor environments. The results revealed that outdoor cardiorespiratory fitness training provided participants with lower training intensity during the active exercise phase and higher heart rate during the stretching phase compared to indoor training. The participants paid more attention to the slope, length, pavement, Spaciousness, and width of the trails and the circuitous route. The change of the visual atmosphere and the scenery for the environmental factors were the important factors to motivate the participants to train. The results of the study could assist participants to understand a favorable cardiorespiratory training environment and design a suitable training program, as well as provide a model for trail planning and design for government.